Reconciling the Issues of Shifting and Permanent Cultivation: An Empirical Study of Mizoram, Eastern Extension of Himalaya, India - Vishwambhar Prasad Sati (Caraka Tani: Journal of Sustainable Agriculture, 2022)
Mizoram is an underdeveloped state where agriculture, dominated by shifting cultivation is the main occupation and a source of income for nearly half of the population. Therefore, this study aimed to examine ‘whether the shifting cultivation is economically viable, or whether permanent cultivation instead has the potential to boost up income and economy of the rural farming community in Mizoram’. To address these questions, a household-level survey was conducted in 2018 based on a case study of 16 villages, comprising two each from eight districts. A purposive random sampling method was applied to select households and a structured questionnaire was developed with questions pertaining to various aspects of shifting and permanent cultivation. Mizoram only has approximately 5% of arable land, of which shifting cultivation accounts for more than 50%. In the past, the output from shifting cultivation was able to feed the farming communities called Jhumias but the area, production and productivity of the crops have recently decreased considerably. This is primarily accountable for the increasing food needs and decreasing crop production, as well as climate variability, land ownership rights and lifestyle change. Meanwhile, the production and productivity of crops grown using permanent cultivation are comparatively higher. It is then suggested that land rights for Jhumias need to be protected for permanent cultivation. The addition of value by commercializing crops will enhance income and effectively boost the economy.